Peranan orang tua terhadap kegiatan belajar mengajar daring kelas 7 di smp negeri 7 yogyakarta - Kartika Yuliana; Enik Nurkholidah (Indonesian Counselor Association (IKI), 2022)
This study aims to determine the role of parents in students' online teaching and learning activities. This research was conducted at SMP Negeri 7 Yogyakarta in the academic year 2021/2022. This study uses a qualitative approach. Selection of informants using purposive technique. The data in this study are qualitative data sourced from primary data and secondary data. Data collection techniques are interviews, observation and documentation. The data analysis technique used is descriptive qualitative. This study also uses data triangulation techniques because the data are obtained from different sources and provide mutual reinforcement, namely from SMP Negeri 7 Yogyakarta. The results showed that the role of parents in online teaching and learning activities in grade 7 at SMP Negeri 7 Yogyakarta for the academic year 2021/2022 was in the form of accompanying, monitoring, reminding, communicating, motivating, and providing facilities to students in online learning